Journalistic Podcasts by Women as an Aesthetic Experience of Recognition in the Context of Transmedia Narratives and Algorithms - de Barros, Laan Mendes [UNESP] (2024)
This paper articulates communication, media ecology and aesthetic experience and problematizes tensions related to the control mechanisms of streaming and the possibilities of sensible interaction, recognition and political and social engagement on podcasts. Contrasts, then, the existence of user data monitoring in the platform era with podcast formats that give voice to minority, female agendas, such as insurgent experiences of (re)existence. There-fore, it discusses the issue of recognition and emancipation of spectators in the context of network society, which is configured in a complex network of interactions and recreations, consensus and dissensus, sharing and belonging. The paper analyzes productions made by women, such as “partition of the sensible” and aesthetic experience, which build a “sensus communalis” even in environments governed by algorithms. It uses criteria of hermeneutic, interpretation and appropriation processes by the public, to problematize the phenomenon of podcasting from a case study of the podcasts Mamilos and Conversa de Portão. In this way, it combines a theoretical approach with empirical discussions about the phenomenon of podcasts.